ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN KRITERIA WATSON DITINJAU DARI SEGI GENDER - Kumala Sari, Sindy Putri; Wulantina, Endah (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
This study aims to describe the types of student errors and the factors that cause students to make mistakes in solving word problems based on Watson's criteria in terms of gender. The research method used is descriptive qualitative. The subjects of this study were class VIII students of SMP Muhammadiyah 1 Sekampung Udik consisting of male students who made the most types of mistakes and could communicate well and female students who had the most types of mistakes and were able to communicate well. The results of the analysis and discussion that have been carried out show that female students make 5 types of mistakes, namely inappropriate procedures (19.56%), missing conclusions (26.08%), level response conflicts (13.04%), skills hierarchy problems (17 .39%), and other than the seven categories above (23.91%). Meanwhile, male students made 6 types of errors, namely incorrect data (18.91%), inappropriate procedures (13.51%), lost conclusions (18.91%), response level conflicts (8.10%), problems skills hierarchy (10.81%), and other than the seven categories above (29.72%).